ANALISIS EFEKTIVITAS BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERHADAP PAJAK DAERAH DI KABUPATEN MINAHASA TENGGARA - Koho, Clever Clinton; Sabijono, Harijanto; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
Tax inspection is a series of activities to search, collect, process data and or other information to test compliance fulfillment of tax obligations and for other purposes in order to implement the provisions of tax laws and regulations. This matter is also motivated with the current tax law in Indonesia in implementing tax collection with self assessment system. Cost acquisition of Land and Building Rights is one of the local taxes that has a major contribution as local tax revenue. The used analysis method in this research is descriptive with qualitative approach. The results used in this study show that the effectivity of Customs Acquisition Rights on Land and Buildings in 2015-2017 is considered very effective. This means that the performance of the Government in Southeast Minahasa Tenggara is very good because it can meet the targets that have been determined, and the government of Southeast Minahasa Tenggara should continue to maintain it.Keywords: Effectivity, Cost Acquisition of Land and Building Rights, Local Tax